Assessing friction in silk-like finished polyester fabrics. Issue 1 (2nd January 2018) - Carrera-Gallissà, Enric; Capdevila, Xavier; Escusa, Mercedes
Abstract: The influence of the silk-like finishing process on the frictional properties of polyester fabrics was examined by assessing fibre-to-metal friction through parameter R in a 100% polyester woven fabric processed under variable conditions of NaOH concentration and vaporization time. The alkali concentration influenced static and dynamic friction in the fabric, whereas the vaporization time only affected static friction. Process variables can be used to predict the frictional performance of silk-like finished fabrics via parameter R for dynamic friction. Fabric weight loss by effect of the silk-like finishing treatment influences the coefficient of fibre-to-metal friction. Industrially, the silk-line finishing process is typically monitored through weight loss in the finished fabric. As shown here, however, it can also be monitored by assessing changes in fabric surface via the dynamic friction parameter R .